An Approach for Ushering Logistic Regression Early in Introductory Analytics Courses - Kunene, Niki; Toskin, Katarzyna (Information Systems Education Journal, 2022)
Logistic regression (LoR) is a foundational supervised machine learning algorithm and yet, unlike linear regression, appears rarely taught early on, where analogy and proximity to linear regression would be an advantage. A random sample of 50 syllabi from undergraduate business statistics courses shows only two percent of the courses included LoR. Conceivable reasons for this dearth of LoR content is likely related to topic complexity, time constraints, and varying degrees of tool ease of use and support. We propose that these constraints can be countered by: [1] introducing logistic regression early, [2] informed tool selection prioritizing ease of use with comprehensive output, and [3] using/developing innovative, accessible, and easy to understand concept learning aids. This approach would leverage the proximity to linear regression and probability readily embed distributed practice for student understanding of a foundational technique.
Keywords: Business Administration Education; Comparative Analysis; Concept Formation; Course Content; Course Descriptions; Goodness of Fit; Institutional Characteristics; Introductory Courses; Private Colleges; Probability; Regression (Statistics); State Universities; Statistics Education; Teaching Methods; Two Year Colleges; Undergraduate Students; Universities; Usability; dept.bis; peer-reviewed; ⛔ No DOI found

The Evolving Landscape of International Consumer Data Privacy Compliance. - Pisano, Mark; Smith, Robert A.; Badr, Kauther S. (ACET Journal of Computer Education & Research, 2022)
Keywords: dept.bis; dept.mgt; peer-reviewed; ⛔ No DOI found

Property Management – An Industry of Fragmented Technology Solutions - Bassett, Richard; Pisano, Mark (Information Technology and Management Science, 2022)
Successful property management, which can be done by individual owners or by professional property managers, has numerous interrelated complex business processes: tenant attraction, screening, leasing, tenant move-in, property maintenance, retention/lease renewals, tenant move-out, and reputation management. Property managers must be highly skilled communicators and thoroughly understand the legal implications of housing and contract law in their operating environments. The lack of affordable solutions available to small and mid-sized property managers drives their use of fragmented technology solutions provided by numerous technology vendors that employ redundant data-gathering methods, putting them at a competitive disadvantage. This research paper explores the information systems needs of property managers in contrast to the solutions available to them in the marketplace.
Keywords: Automated business process; dept.bis; fragmented technology solutions; peer-reviewed; property leasing; property management; property marketing